2015
DOI: 10.1523/jneurosci.0600-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Laminar Profile and Physiology of the α Rhythm in Primary Visual, Auditory, and Somatosensory Regions of Neocortex

Abstract: The functional significance of the ␣ rhythm is widely debated. It has been proposed that ␣ reflects sensory inhibition and/or a temporal sampling or "parsing" mechanism. There is also continuing disagreement over the more fundamental questions of which cortical layers generate ␣ rhythms and whether the generation of ␣ is equivalent across sensory systems. To address these latter questions, we analyzed laminar profiles of local field potentials (LFPs) and concomitant multiunit activity (MUA) from macaque V1, S1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

27
167
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(196 citation statements)
references
References 66 publications
27
167
2
Order By: Relevance
“…Our finding that α-oscillations are related to activity in deep layers agrees well with various laminar studies reporting α-activity in infragranular layers (6,7,9,12). However, we did not find a relation between the attention effects in BOLD and α-power in the deep layers.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our finding that α-oscillations are related to activity in deep layers agrees well with various laminar studies reporting α-activity in infragranular layers (6,7,9,12). However, we did not find a relation between the attention effects in BOLD and α-power in the deep layers.…”
Section: Discussionsupporting
confidence: 91%
“…This difference suggests multiple neural processes related to α-activity within the visual cortex as measured at the scalp with EEG. Although some studies have demonstrated multiple α-sources in the early visual regions in both supra-and infragranular layers (9,12), others suggested a predominance of α-activity in deep layers (6,11,31). The results here are in line with multiple α-sources in both supraand infragranular layers, in which, in our task, only the α-source or sources in more superficial layers are modulated by attention.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Alpha generators have been found in different layers of both striate and extra-striate visual areas (Bollimunta et al, 2008(Bollimunta et al, , 2011Mo et al, 2011;Haegens et al, 2015;van Kerkoerle et al, 2014), and are known to be modulated in activity by both cortico-cortical and recurrent thalamo-cortical (TC) communication (Steriade et al, 1990), influenced by thalamic nuclei such as the lateral geniculate nucleus (LGN), the pulvinar nucleus, and the thalamic reticular nucleus (TRN). Evidence is growing that these different thalamic nuclei play different roles in sensory information processing, both spatially (i.e., across the visual hierarchy) and temporally (i.e., during early feedforward and later feedback processing), raising the possibility that aberrant alpha-band activity in visual cortices may in part reflect aberrant TC-interactions.…”
mentioning
confidence: 99%